Pengaruh Model Discovery Learning Berbantuan Liveworksheets Terhadap Hasil Belajar Pendidikan Pancasila Kelas Iv Upt Spf Sd Negeri Kapota Yudha Makassar - Nurkhalisa Salsabila (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aimed to analyze the effect of the Discovery Learning model integrated with Liveworksheets on the Pancasila Education learning outcomes of fourth-grade students at UPT SPF SD Negeri Kapota Yudha Makassar. The study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 51 students selected through purposive sampling, including 26 students in Class IV-A as the experimental group and 25 students in Class IV-B as the control group. Data were collected through pretests, posttests, and classroom observations, then analyzed using descriptive statistics and inferential statistics with ANCOVA. The results indicated that the implementation of the Discovery Learning model integrated with Liveworksheets was successfully carried out according to the instructional syntax and had a significant positive effect on students' Pancasila Education learning outcomes.